PERAN DUKUNGAN SOSIAL BAGI SUBJECTIVE WELL BEING LANSIA YANG TINGGAL DI PANTI SOSIAL - Setyaningrum, Dyah Titi (PSIKOLOGI KONSELING, 2023)
Elderly people who receive social support are be able to have subjective well being so that they predicted to live a more productive and happier. This research aims to test which form of Social Support, sourced from the family or social institutions, who have a greater role in the Subjective Well-Being of elderly people who living in  the social institutions. This research uses Social Support theory (Sarafino, 2019) and Subjective Well-Being (Diener, 2003), with quantitative research. The research subjects were 32 elderly people. The sampling technique used is simple random sampling. The validity test was measured using Jamovi with CFA (Confirmatory Factor Analysis) criteria, and the reliability test used the McDonald's Omega value with a score of 0.815 for the Social support measuring tool and a Cronbach alpha score of 0.783 for the Subjective well being measuring tool. Data collection was carried out by reading the questionnaire items one by one to the elderly. Then a statistical test was carried out using JASP version 17 and the results showed that there was a significant influence between social support and subjective well-being with a greater contribution from the social institutions than the family. Of the four types of social support and the two sources of social support, it shows that the type of companionship support that comes from the social institutions and instrumental support that comes from the family have a higher influence. Suggestions from researchers are that the social institutions continues to maintain positive support for the elderly and makes itself available to facilitate religious/spiritual activities and the family remains willing to attend and provide instrumental support to facilitate the physical activity of the elderly in the institutions.